Hodgkin's lymphoma presenting as autoimmune hemolytic anemia - Sohaila Fatima; Wajih A Siddiqui; Abdulrahman Alshehri (SpringerOpen, 2017)
Hodgkin's lymphoma is a B-cell neoplasm, which usually presents with painless lymphadenopathy. Its presentation with autoimmune hemolytic anemia (AIHA) is rare, although the association of AIHA with other lymphoproliferative disorders is well known. Here, we report a case of a patient with warm AIHA who presented in a critical condition to hospital and was diagnosed with HL.